2018
DOI: 10.1038/s41467-017-02759-8
|View full text |Cite
|
Sign up to set email alerts
|

Dot1 regulates nucleosome dynamics by its inherent histone chaperone activity in yeast

Abstract: Dot1 (disruptor of telomeric silencing-1, DOT1L in humans) is the only known enzyme responsible for histone H3 lysine 79 methylation (H3K79me) and is evolutionarily conserved in most eukaryotes. Yeast Dot1p lacks a SET domain and does not methylate free histones and thus may have different actions with respect to other histone methyltransferases. Here we show that Dot1p displays histone chaperone activity and regulates nucleosome dynamics via histone exchange in yeast. We show that a methylation-independent fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
32
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 60 publications
(71 reference statements)
1
32
0
Order By: Relevance
“…These results suggest that the DOT1L binding to the nucleosome might destabilize the nucleosome structure. Consistent with these observations, a recent study showed that DOT1L-bound nucleosome is more readily remodeled by the CHD1 ATP-dependent chromatin remodeler than the nucleosome alone (Lee et al 2018).…”
Section: Dot1l Binding Destabilizes the Nucleosome Structurementioning
confidence: 52%
See 2 more Smart Citations
“…These results suggest that the DOT1L binding to the nucleosome might destabilize the nucleosome structure. Consistent with these observations, a recent study showed that DOT1L-bound nucleosome is more readily remodeled by the CHD1 ATP-dependent chromatin remodeler than the nucleosome alone (Lee et al 2018).…”
Section: Dot1l Binding Destabilizes the Nucleosome Structurementioning
confidence: 52%
“…Furthermore, these results add another layer of complexity to the cross-talk, where H2B ubiquitination regulates the DOT1L-mediated nucleosome destabilization in addition to histone H3 Lys79 methylation. As previous works showed that H2B ubiquitination plays important roles in transcription elongation and nucleosome dynamics, DOT1L-mediated DNA unwrapping might facilitate this process (Wu et al 2014;Krajewski et al 2018;Lee et al 2018). At this moment, it is not clear how DOT1L binding induces the detachment of DNA with the concomitant disorder of the parts of histones.…”
Section: Dot1l Binding Destabilizes the Nucleosome Structurementioning
confidence: 93%
See 1 more Smart Citation
“…Histone acetylation is increased in the absence of the deacetylase HDAC1, and histone acetylation has been previously linked to DOT1L recruitment through the YEATS domain transcription elongation proteins AF9 and ENL (Li et al , ; Kuntimaddi et al , ; Erb et al , ; Wan et al , ). Very recently, preferential Dot1 binding to acetylated H4K16 has been shown, and the histone acetyltransferase Sas2 was found to be a positive regulator of H3K79 methylation in yeast, probably via acetylation of H4K16 (Lee et al , ). Our identification of Rpd3/HDAC1 as a regulator of DOT1L underscores the intimate relationship between histone acetylation and H2Bub and H3K79me and provides evidence for a specific HDAC involved in the crosstalk: HDAC1.…”
Section: Discussionmentioning
confidence: 99%
“…Current evidence from studies in yeast and with DOT1L in vitro suggest that H2Bub1 promotes the activity of Dot1 not by increased recruitment, but instead by physically corralling the enzyme into a productive binding orientation, promoting all methylation steps from unmethylated H3K79 to H3K79me1, -me2 and -me3 ( 19 , 27 ). As a consequence, co-transcriptional H2Bub1 deposition leads to a high methylation state (H3K79me3) in transcribed regions, whereas in intergenic regions or silent chromatin, where H2Bub1 is low, only lower methylation states (H3K79me1 and -me2) are deposited ( 20 , 28 , 29 ). Recently, several additional mechanisms of regulation of Dot1 have been described, some of which also impinge on the H2Bub-H3K79me crosstalk ( 20 ).…”
Section: Introductionmentioning
confidence: 99%